Sulphur isotope stratigraphy of drill cuttings and stratigraphic correlation of Permian-Triassic evaporites - Salisbury, Jack; Gröcke, Darren R.; McKie, Tom (Frontiers in Earth Science, 2023)
The stratigraphy of the European late Permian-Triassic commonly lacks chronostratigraphic constraint due to the scarcity of diagnostic fossils for biostratigraphy. This is particularly true for the United Kingdom, and as a result, stratigraphic correlation within and between sedimentary basins is primarily reliant on lithostratigraphy. Evaporitic sulphate can be used to develop time series of δ34Sevap data that can be utilised for stratigraphic correlation. However, the availability of continuous drillcore is limited, whilst drill cuttings are commonly acquired but are widely overlooked for stable isotope stratigraphy. We derive a δ34Sevap record from drill cuttings from the southern North Sea Basin, and successfully correlate it with an equivalent published δ34Sevap record from a continuous drillcore in the Cleveland Basin, Yorkshire, United Kingdom. We have chosen seven points in the δ34Sevap records for stratigraphic correlation, defining eight packages of isotopically distinct coeval strata. This is significant, as the ubiquity of drill cuttings presents the opportunity to derive δ34Sevap curves with high geospatial resolution. Equivalent gamma ray logs were used for correlation and compared with the δ34Sevap curves. The correlations agree relatively well, however, the δ34Sevap correlation permits the development of more robust chronostratigraphic constraints. Specifically, the δ34Sevap records constrain the age of the Bunter Shale and Bunter Sandstone in the western Southern North Sea to the latest Permian. This has significant implications for understanding the stratigraphy and palaeogeographic evolution of United Kingdom Permian-Triassic sedimentary basins, and may have economic implications, since the Bunter Sandstone is being considered as a potential reservoir for CO2 storage in the United Kingdom sector.